2018
DOI: 10.1177/0081246318775547
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the relationship between motivational beliefs, cognitive learning strategies, and academic performance of teacher education students

Abstract: Although self-regulated learning has received much attention over the past decades, research on how teacher education students regulate their own learning has been scarce, particularly in third world countries. In the present study, we examined the structural relationships between motivational beliefs, cognitive learning strategies, and academic performance among teacher education students in Uganda. The sample comprised of 1081 students selected from seven universities. Data were collected using several subsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…1-Task value significantly predicted SRL as observed in most studies [23,26,30, 32] 2-Mediator roles of task value and SRL (n=2) 2-Task value was significant mediator between self-efficacy and SRL as reported in a study [24]; SRL significantly mediated the control of learning beliefs and task value as reported in a study [37] 3-Correlation between task value and SRL (n=1) 3-Task value was positively and significantly linked to SRL as reported in a study [22] Extrinsic goal orientation (n=8) 1-Effect of extrinsic goal orientation on SRL (n=5) 1-Extrinsic goal orientation was negatively related to SRL as reported in some studies [25,33]; Extrinsic goal orientation positively predicted SRL as observed in several studies [26,32,34] 2-Correlation between extrinsic goal orientation and SRL (n=2) 2-Extrinsic goal orientation was negatively associated with SRL as observed in a study [19]; Extrinsic goal orientation was positively associated with SRL as reported in a study [36] 3-Effect of SRL on extrinsic goal orientation (n=1) 3-SRL had a positive and significant impact on the academic motivation including extrinsic goal orientation as observed in a study [28] Test anxiety (n=6) 1-Correlation between test anxiety and SRL (n=3) 1-Test anxiety was insignificantly or negatively linked to SRL as observed in some studies [18,22,32] 2-Effect of test anxiety on SRL (n=3) 2-Insignificant or negative effect of test anxiety in predicting SRL as observed in some studies [25,26]; Test anxiety was significant and positive predictor of SRL as reported in a study [27] Control of learning beliefs (n=5) 1-Effect of control of learning beliefs on SRL (n=3) 1-Control of learning beliefs significantly and positively predicted SRL as reported in some studies [26,32]; control of learning beliefs was not significant predictor of SRL was observed in a study [25] 2-Correlation between control of learning beliefs and SRL (n=1) 2-Control of learning beliefs were moderately associated with SRL as reported in a study [18] 3-Mediator role of SRL between motivational constructs (n=1) 3-SRL significantly mediated control of learning beliefs and task value as reported in a study [25]…”
Section: -Effect Of Task Value On Srl (N=6)mentioning
confidence: 83%
“…1-Task value significantly predicted SRL as observed in most studies [23,26,30, 32] 2-Mediator roles of task value and SRL (n=2) 2-Task value was significant mediator between self-efficacy and SRL as reported in a study [24]; SRL significantly mediated the control of learning beliefs and task value as reported in a study [37] 3-Correlation between task value and SRL (n=1) 3-Task value was positively and significantly linked to SRL as reported in a study [22] Extrinsic goal orientation (n=8) 1-Effect of extrinsic goal orientation on SRL (n=5) 1-Extrinsic goal orientation was negatively related to SRL as reported in some studies [25,33]; Extrinsic goal orientation positively predicted SRL as observed in several studies [26,32,34] 2-Correlation between extrinsic goal orientation and SRL (n=2) 2-Extrinsic goal orientation was negatively associated with SRL as observed in a study [19]; Extrinsic goal orientation was positively associated with SRL as reported in a study [36] 3-Effect of SRL on extrinsic goal orientation (n=1) 3-SRL had a positive and significant impact on the academic motivation including extrinsic goal orientation as observed in a study [28] Test anxiety (n=6) 1-Correlation between test anxiety and SRL (n=3) 1-Test anxiety was insignificantly or negatively linked to SRL as observed in some studies [18,22,32] 2-Effect of test anxiety on SRL (n=3) 2-Insignificant or negative effect of test anxiety in predicting SRL as observed in some studies [25,26]; Test anxiety was significant and positive predictor of SRL as reported in a study [27] Control of learning beliefs (n=5) 1-Effect of control of learning beliefs on SRL (n=3) 1-Control of learning beliefs significantly and positively predicted SRL as reported in some studies [26,32]; control of learning beliefs was not significant predictor of SRL was observed in a study [25] 2-Correlation between control of learning beliefs and SRL (n=1) 2-Control of learning beliefs were moderately associated with SRL as reported in a study [18] 3-Mediator role of SRL between motivational constructs (n=1) 3-SRL significantly mediated control of learning beliefs and task value as reported in a study [25]…”
Section: -Effect Of Task Value On Srl (N=6)mentioning
confidence: 83%
“…Among the SCCT structures examined, the students’ academic achievement in this study was most influenced, in terms of self-regulating learning strategies, by the changes in organizing and expansion strategies, which is in line with the results obtained by Muwonge et al (2018). They stated that the organizing strategy is one of the best and most complete types of learning strategies [14]. In addition, the strategy of semantic expanding through addition of new information to link to previous information should always be considered by lecturers in teaching skills.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the findings of this study, Muwonge et al, in their study on the self-regulation and motivational learning strategies among 1081 students from seven universities in Uganda, stated that motivational strategies influenced students’ academic achievement only through affecting critical thinking strategies and organizing skills. Therefore, educational interventions to improve the academic performance of students should focus on increasing the motivation of learners and enhance their use of cognitive learning strategies [14]. Thus, it can be said that students who have a high motivation to obtain a better score demonstrate more effort, better organize their information, have better time management, and show better performance [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the belief that their actions directly influence their success or failure must also be accompanied by appropriate learning strategies for students to be successful (Rotgans and Schmidt, 2012). For example, Muwonge et al (2019) found that students with greater COLB also had higher GPA scores and that the favorable outcome was most significantly mediated by critical thinking and organization. Meaning, the students who believed their efforts would determine their success employed the necessary critical thinking and organizational strategies to retain the material.…”
Section: Control Of Learning Beliefsmentioning
confidence: 99%